2011
DOI: 10.1007/s10404-011-0773-x
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental measurement on tangential momentum accommodation coefficient in a single microtube

Abstract: The tangential momentum accommodation coefficient (TMAC) was investigated experimentally from the mass flow rate through a single microtube under the slip flow and the early part of the transition regime. The measurements were carried out by the constant-volume method under the mean Knudsen number smaller than 0.3, which is based on the mean pressure of the inlet and the outlet of the microtube, to apply the second-order slip boundary condition. To measure TMACs on various materials, quite large microtube was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 21 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…It is found that the simulated plenum pressure matches the experimental plenum pressure only when a slip boundary condition is used with the recommended value of α u = 0.9 for both N 2 and Ar [38][39][40][41][42][43][44][45][46]. The plenum pressure is very slightly overestimated with a no-slip boundary condition, and FIGURE 3 | Experimental plenum pressure (blue line) and chamber pressure (black line) measurements against mass flow rate of Ar into PR.…”
Section: Set 1: Pr Laboratory Conditionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is found that the simulated plenum pressure matches the experimental plenum pressure only when a slip boundary condition is used with the recommended value of α u = 0.9 for both N 2 and Ar [38][39][40][41][42][43][44][45][46]. The plenum pressure is very slightly overestimated with a no-slip boundary condition, and FIGURE 3 | Experimental plenum pressure (blue line) and chamber pressure (black line) measurements against mass flow rate of Ar into PR.…”
Section: Set 1: Pr Laboratory Conditionmentioning
confidence: 91%
“…Measurements of α u are typically performed by tracking the flow of gas through a microchannel. These experiments [38][39][40][41][42][43][44][45][46] are performed over a wide range of pressures at room temperature, and use microchannels with different shapes and diameters, constructed of various materials and surface treatments. Since the α u of each gas remains roughly constant across different conditions and flow regimes, it is justified to use the mean value of α u for each gas in the simulations.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…To check the fraction of each component and other residual gases, the gas in the downstream chamber was sampled through a variable leak valve and analyzed by a quadrupole mass spectrometer (Pfeiffer Vacuum, QMS 200) with a pumping station before and after each measurement of the mass flow rate. Due to the connection to the QMS, the volume of the downstream chamber was a little increased from the previously reported value 15) to Vo [cm 3 ] = 450.26 +0.017…”
Section: A Experimental Proceduresmentioning
confidence: 83%
“…The measurement principle and setup is explained in details in Ref. 15 and a schematic of the setup is shown in Fig. 1.…”
Section: A Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation